2017
DOI: 10.1021/acsnano.6b06913
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Functionalization by Cycloaddition Reactions of Pristine Defect-Free Graphene

Abstract: Based on a low-temperature scanning tunneling microscopy study, we present a direct visualization of a cycloaddition reaction performed for some specific fluorinated maleimide molecules deposited on graphene. Up to now, it was widely admitted that such a cycloaddition reaction can not happen without pre-existing defects. However, our study shows that the cycloaddition reaction can be carried out on a defect-free basal graphene plane at room temperature. In the course of covalently grafting the molecules to gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 38 publications
3
65
1
Order By: Relevance
“…However, in most cases the properties of graphene are supposed to be tailored for satisfying different requirements in industries. Tuning properties of graphene can be realized by several defects modulations approaches, including particle irradiation [326328], thermal annealing [329,330], chemical reaction [331,332] and strain treatment [333,334], as summarized in Table 2.…”
Section: Modulation Of Structural Defects In Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…However, in most cases the properties of graphene are supposed to be tailored for satisfying different requirements in industries. Tuning properties of graphene can be realized by several defects modulations approaches, including particle irradiation [326328], thermal annealing [329,330], chemical reaction [331,332] and strain treatment [333,334], as summarized in Table 2.…”
Section: Modulation Of Structural Defects In Graphenementioning
confidence: 99%
“…Daukiya et al [332] successfully performed cycloaddition reactions on graphene by depositing maleimide derivative molecules at room temperature. Experimental results indicate that both (1,4) and (1,2) cycloadditions are possible on freestanding graphene, but only the (1,2) cycloaddition could be activated for SiC (0001)-supported graphene.…”
Section: Modulation Of Structural Defects In Graphenementioning
confidence: 99%
“…Maleimides containing pentafluoro and trifluoro groups on aromatics were copolymerized with vinyl ethers by Hendlinger et al whereas Jain et al copolymerized N ‐(4‐fluoro phenyl) maleimide with methyl methacrylate. Daukiya et al showed the use of N ‐(3,4‐trifluoro phenyl) maleimide with highly nonreactive graphene. Fluorinated oligomers with maleimides were first reported by Beaune et al with C 6 F 13 chains .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] For example, Haddon and co-workerss howed that graphite/graphenec an serve as a diene by reacting with tetracyanoethylene (TCNE) at room temperature. [7][8][9][10] For example, Haddon and co-workerss howed that graphite/graphenec an serve as a diene by reacting with tetracyanoethylene (TCNE) at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The Braunschweig group showed that cyclopentadiene can covalently react with ag raphene surface under high pressure Diels-Alder conditions. [10] Inverse electron demand Diels-Alder reactions (IEDDA) have been the subjecto fc onsiderable interest in biorthogonalc onjugations. [9] More recently, Simon and co-workersd emonstrated the direct visualizationo ft he covalent cycloaddition of maleimide derivatives on the defect-free basal graphene plane by scanning tunneling microscopy.…”
Section: Introductionmentioning
confidence: 99%